ISLAMIC EDUCATION AND LOCAL POLITICS: Analysis of Regent Regulations Regarding Local Content Education - Dr. Munawir; Suheri, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
Education and Politics feels very difficult to separate. Like Michael Foult's statement that it is impossible to separate knowledge by leaving power, and vice versa it is impossible for power to work without knowledge. Power works in the process of forming knowledge which is a form of culture. Education is not possible to run well in accordance with the ideal concept by releasing total power with no interference from power, moreover the capacity of educators is very limited so that they are unable to manage students well in a comprehensive and effective manner. Religious education in the process will not be able to break away from the social and political problems that exist around it, including those in Bondowoso district in the implementation of the development of Islamic religious education. The aim of this research is to reveal and analyze the implementation, implications for regent regulation number 28 of 2011. This study uses a qualitative approach, while in the data collection researchers use various methods, namely: observation, in-depth interviews and documentaries. Based on data analysis, several conclusions were found; first implementation of regent regulation number 28 of 2011 went well, as evidenced by the enthusiasm of officials, principals and Islamic Education teachers in addressing the contents of the regulation. Secondly, regent regulation number 28 of 2011 on the Qur'anic Reading and Writing has very significant implications for students in developing Islamic religious education. Third, in general the citizens and religious leaders welcomed and responded positively to the enactment of regent regulations regarding reading the Quran.